Maternal Mortality Among Indigenous Peoples. Issue 1 (January 2021) - Heck, Jennifer L.
Abstract : Indigenous women have more adverse pregnancy outcomes when compared to women of other ethnic groups. Our guest global health and nursing columnist, Dr. Heck, highlights these disparities in the United States and across the world.